2015
DOI: 10.1007/jhep01(2015)006
|View full text |Cite
|
Sign up to set email alerts
|

A fresh look at keV sterile neutrino dark matter from frozen-in scalars

Abstract: Sterile neutrinos with a mass of a few keV can serve as cosmological warm dark matter. We study the production of keV sterile neutrinos in the early universe from the decay of a frozen-in scalar. Previous studies focused on heavy frozen-in scalars with masses above the Higgs mass leading to a hot spectrum for sterile neutrinos with masses below 8 − 10 keV. Motivated by the recent hints for an X-ray line at 3.55 keV, we extend the analysis to lighter frozen-in scalars, which allow for a cooler spectrum. Below t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(81 citation statements)
references
References 106 publications
4
75
2
Order By: Relevance
“…This is justified by kinematical arguments and by the low 36 For detailed comments on this assumption, see [676,730] and references therein. 37 For the case of mS < vEW studies on the level of particle number densitites can be found in [683].…”
Section: Necessary Approximationmentioning
confidence: 99%
“…This is justified by kinematical arguments and by the low 36 For detailed comments on this assumption, see [676,730] and references therein. 37 For the case of mS < vEW studies on the level of particle number densitites can be found in [683].…”
Section: Necessary Approximationmentioning
confidence: 99%
“…2016;Merle & Schneider 2015), thereby strongly pushing such scenarios. Other settings, where sterile neutrinos are produced by decays of, e.g., scalar particles (see a few concrete examples in Shaposhnikov & Tkachev 2006;Kusenko 2006;Petraki & Kusenko 2008;Merle et al 2014;Merle & Totzauer 2015;Klasen & Yaguna 2013;Adulpravitchai & Schmidt 2015;Shakya 2016;König et al 2016), are largely unconstrained by present X-ray observations, since they could in principle operate even without active-sterile mixing. Note that the corresponding parent in such Scalar Decay (SD) models must themselves be coupled to the Standard Model, typically via the Higgs sector.…”
Section: Introductionmentioning
confidence: 99%
“…From the observed fluxes, and with the assumption that the sterile neutrinos constitute all of the dark matter, the inferred best-fit vacuum mixing angles are sin 2 2θ v ≈ 7 × 10 −11 . While the existence of this line in terms of statistical significance, as well as its interpretation as having a dark matter origin are still up for debate [83][84][85][86][87][88][89][90][91][92][93][94], the possibility remains intriguing, and various sterile neutrino dark matter models can have their parameters tailored to fit this particular scenario [29,30,[32][33][34][35][36]38]. Future Xray telescopes such as ASTRO-H and ATHENA, as well as microcalorimeter sounding rocket experiments such as Micro-X [95,96], with their high energy resolution, could help settle the verdict on this case one way or the other [97].…”
Section: The 355 Kev X-ray Linementioning
confidence: 99%